1993
DOI: 10.1161/01.cir.88.5.2045
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin versus heparin to prevent myocardial infarction during the acute phase of unstable angina.

Abstract: Background. Antiplatelet therapy with aspirin and antithrombotic therapy with heparin both prevent the complications of unstable angina; however, no definitive data exist on the relative clinical efficacy of the two drugs.Methods and Results. Aspirin (325 mg bid) or heparin (5000-U intravenous bolus followed by a perfusion titrated to the APTT) were compared in a double-blind randomized trial of 484 patients in two cohorts enrolled sequentially. The study was initiated at admission to hospital at a mean of 8.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
57
0
5

Year Published

1998
1998
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(62 citation statements)
references
References 19 publications
0
57
0
5
Order By: Relevance
“…[435][436][437][438][439][440] The results of studies that compared the combination of ASA and heparin with ASA alone are shown in Figure 10. In the trials that used UFH, the reduction in the rate of death or MI during the first week was 54% (p ϭ 0.016), and in the trials that used either UFH or LMWH, the reduction was 63%.…”
Section: Unfractionated Heparinmentioning
confidence: 99%
“…[435][436][437][438][439][440] The results of studies that compared the combination of ASA and heparin with ASA alone are shown in Figure 10. In the trials that used UFH, the reduction in the rate of death or MI during the first week was 54% (p ϭ 0.016), and in the trials that used either UFH or LMWH, the reduction was 63%.…”
Section: Unfractionated Heparinmentioning
confidence: 99%
“…Antithrombotic strategies for the acute management of patients with unstable angina/non-Q-wave myocardial infarction (MI) include a combination of an antithrombin agent, usually an intravenous infusion of unfractionated heparin, and an antiplatelet agent, usually oral aspirin. [7][8][9][10][11][12] Beyond aspirin, optimal outpatientphase therapy for patients presenting with unstable angina/ non-Q-wave MI remains to be defined. 13 …”
mentioning
confidence: 99%
“…For these groups of patients, accepted treatments include aspirin, 1 heparin, 2 and beta blockers, 3 as well as conventional anti-anginal treatments. Despite these treatments, patients with ACS remain at high risk of further ischaemic events that lead to death, new MI and recurrent angina.…”
mentioning
confidence: 99%